The American ascendancy : how the United States gained and wielded global dominance - Hunt, Michael H. (H. Eugene and Lillian Youngs Lehman series., 2007)
A simple question lurks amid the considerable controversy created by recent U.S. policy: what road did Americans travel to reach their current global preeminence? Taking the long historical view, Michael Hunt demonstrates that wealth, confidence, and leadership were key elements to America's ascent. In an analytic narrative that illuminates the past rather than indulges in political triumphalism, he provides crucial insights into the country's problematic place in the world today.